Исследование возможности минимизации вычислительной сложности криптографических алгоритмов путем их распараллеливания - Кривошеева, Галина Михайловна (Eastern-European Journal of Enterprise Technologies, 2009)
Necessity of increase in speed and productivity of cryptography algorithms demands application of new methods. For solution of the given task possibility application of parallel technologies is researched.